Study on the Factors Influencing the Separation of Sr and Nd in Sediments by Ion Exchange Resin - YIN Peng; HE Qian; HE Hui-jun; ZHAO Zhi-qi (Yankuang ceshi, 2018)
BACKGROUND In geological studies, Sr and Nd isotopes are classical isotopic dating and tracer systems. OBJECTIVES The traditional separation method usually uses the AG50W-X8 resin to elute and separate Sr and REEs in sediments, and then uses Sr-special resin and Ln-special resin to purify Sr and Nd, respectively. However, this method has lower recovery of REEs (only 50%) for sediments with high Fe content. METHODS In addition, height and elution acid species of AG50W-X8 resin, Sr resin elution acid volume, and Ln resin washing ways have impacts on the separation of Sr and Nd. In this work, in order to investigate the effect of these factors on the separation of Sr and Nd in detail, we took river sediment (GBW07309) as an example. RESULTS The results showed that (1) high Fe content significantly affected the separation effect of Sr and Nd, and AG1-X8 resin could effectively remove Fe; (2) using 1 mL AG50W-X8 resin and HNO3 as the eluting acid, the separation effect of Sr and REEs was the best; (3) Sr and Rb could be effectively separated when the elution acid volume of Sr-special resin reaches 15 mL; (4) Nd was separated well without trailing phenomenon when gravity column method was used to wash the Ln-special resin. CONCLUSIONS This method solves the Fe interference during separation of Sr and Nd. More than 99% of K, Na, Ca, Mg, Fe, Rb, and Sm were removed, which fully satisfied the requirements for the analysis of Sr and Nd isotopes. This paper provides more detailed empirical data for the separation of Sr and Nd isotopes in sediments by ion exchange resin method.